Talag-Bahay an autonomy-generative healthcare living lab centering on the research of co-designed domotic apartments - Flordeliz, Alexandria Kiara M.; Lacson, David Xander T. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
Independent living is a continuing challenge for persons with mobility, visual, and/or
auditory functional difficulty as there is a lack of effort geared towards the design of
living spaces that mitigate the challenges attached to it, especially within the
Philippine context. To raise the degree of autonomy felt by this population as they
accomplish day-to-day activities at home, a space dedicated to the research of
accessible, smart living spaces is then necessitated. This shall be addressed through a
Healthcare Living Lab, an open innovation approach to a research center that
facilitates co-design and works within the paradigm of healthcare. As such, the
overarching goal of this study is to design an autonomy-generative Healthcare Living
Lab centering on the research of co-designed Domotic Apartments. Integrating
research into the dimension of healthcare, this architectural project is argued to raise
the degree of autonomy experienced by persons with mobility, vision, and hearing
impairments as they perform basic activities of daily living tasks thereby promoting
independent living.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Disabilities; Domotic home; Health Services; Medical care